ALTERNATIF SPLINTING PADA KEGOYANGAN GIGI AKIBAT PENYAKIT PERIODONTAL - Astuti, Lilies Anggarwati (Jurnal Ilmiah As-Syifaa, 2015)
Periodontal disease is a disease of inflammation of the tissues around the tooth that originated from inflammatory gingival and continues to the periodontal structures other periodontal ligament and cementum, and the alveolar bone. Loosening of the teeth is one of the symptoms of periodontal disease characterized by loss of bonding as well as vertical bone damage. Loosening can be caused by damage to the bone that supports the teeth, trauma from occlusion, and the presence of inflammation of the gingiva to the expansion of the network of supporters who are more patologik and processes in the jaw. Purpose: one of the ways to control and stabilize the loosening of the teeth is splinting. Splinting is indicated on the State loosening teeth degree 3 with severe bone damage. Literature review: Periodontal splint is a tool that can be used for stabilization or loosening of teeth that immobilisasi experience. Splint consists of temporary and permanent splint splint. Indication temporary splint is for stabilization of teeth rocking before and during therapy with the goal to reduce the peridontal trauma at the time of care and speed up the healing process, such as the ligature wire splint. Discharging permanent splint is part of this phase of the restoration or reconstruction phases of periodontal care. Permanent Splint is extremely limited usage. Used when actually used to increase the stability of pressure oklusal. Summary: the selection of the alternatives of periodontal splint adapted on certain conditions, such as economic status and health status of the patient.